Small molecule tools for functional interrogation of protein tyrosine phosphatases. (16th August 2012) - He, Rongjun; Zeng, Li‐Fan; He, Yantao; Zhang, Sheng; Zhang, Zhong‐Yin
Abstract : The importance of protein tyrosine phosphatases (PTPs) in the regulation of cellular signalling is well established. Malfunction of PTP activity is also known to be associated with cancer, metabolic syndromes and autoimmune disorders, as well as neurodegenerative and infectious diseases. However, a detailed understanding of the roles played by the PTPs in normal physiology and in pathogenic conditions has been hampered by the absence of PTP‐specific small molecule agents. In addition, the therapeutic benefits of modulating this target class are underexplored as a result of a lack of suitable chemical probes. Potent and specific PTP inhibitors could significantly facilitate functional analysis of the PTPs in complex cellular signal transduction pathways and may constitute valuable therapeutics in the treatment of several human diseases. We highlight the current challenges to and opportunities for developing PTP‐specific small molecule agents. We also review available selective small molecule inhibitors developed for a number of PTPs, including PTP1B, TC‐PTP, SHP2, lymphoid‐specific tyrosine phosphatase, haematopoietic protein tyrosine phosphatase, CD45, PTPβ, PTPγ, PTPRO, Vaccinia H1‐related phosphatase, mitogen‐activated protein kinase phosphatase‐1, mitogen‐activated protein kinase phosphatase‐3, Cdc25, YopH, mPTPA and mPTPB. Abstract : Protein tyrosine phosphatases (PTPs) are important regulators of cellular signaling and potential drug targets. Potent and specific PTP inhibitors serve as powerful tools for functional analysis of the PTPs and may constitute novel therapeutics in the treatment of human diseases. This review summarizes published compounds that have been shown to display reasonable potency and selectivity against the PTPs.